Overview of Adolescents' Knowledge and Attitudes Related to Clean and Healthy Living Behavior at SMA Negeri 2 Tondano - Lidia Injili Bintang; Bertom Pajung; Richard Palilingan; Merdekawati Weken; Maxi Moleong (Universitas Muhammadiyah Palu, 2026)
Clean and Healthy Living Behavior (PHBS) plays an important role in improving the degree of public health through habituation of healthy behavior from adolescence. Schools are strategic environments in the formation of these behaviors. This study aims to find out the overview of adolescents' knowledge and attitudes towards PHBS at SMA Negeri 2 Tondano. The study used a quantitative descriptive design with a cross-sectional approach. The study population was all students of SMA Negeri 2 Tondano totaling 89 respondents who were taken with a total of sampling. Data was collected through questionnaires and analyzed descriptively with frequency and percentage distributions. Most of the respondents had good knowledge about PHBS as many as 66 respondents (66.7%) and good attitudes as many as 59 respondents (66.3%). A small number have enough knowledge and attitudes to less. The majority of SMA Negeri 2 Tondano students have good knowledge and attitude towards PHBS. Coaching, education, and support for school facilities are needed so that clean and healthy living behaviors can be applied consistently.